Relationship between plasma glutamate and cardiovascular disease risk in Chinese patients with type 2 diabetes mellitus by gender - Li, Ru-Tao; Li, Yang; Wang, Bo-Wen; Gao, Xiao-Qian; Zhang, Jing-Xi; Li, Fan; Zhang, Xiang-Yu; Fang, Zhong-Ze (Frontiers in Endocrinology, 2023)
Objectives: This study aimed to assess the association between plasma glutamate (Glu) and the risk 27 of cardiovascular disease (CVD) in patients with type 2 diabetes mellitus (T2DM) and whether this 28 association differs by gender. 29 Material and Methods: We retrieved clinical information on 1032 consecutive patients with T2DM 30 from a same tertiary care center from May 2015 to August 2016. Glu was quantified by liquid 31 chromatography-tandem mass spectrometry analysis. Glu was converted into a categorical variable 32 based on the median concentration in the whole population, while logistic regression was used to 33 obtain the odds ratio (OR) and 95% confidence interval (CI), and the correlation between Glu and 34 various biochemical indices was analyzed. 35 Results: We found that Glu was positively associated with the risk of CVD in patients with T2DM. 36 This correlation was more significant in women. In T2DM patients, the higher the age, body mass 37 index (BMI), weight and systolic blood pressure (SBP), the lower the glycosylated hemoglobin 38 (HbA1C) concentration and the higher the Glu. In female patients, the correlation between age, 39 weight, BMI, SBP, and plasma Triglycerides (TG), and Glu was also statistically significant. 40 Conclusion: In conclusion, female T2DM patients with high levels of Glu have a higher risk of 41 developing CVD.